Transmission Power Controlled Localization with Topology Building for NLOS Environments. (26th August 2014) - You, Jin-Ho; Jeon, Jong-Hyeok; Lee, Tae-Hyung; Kwon, Young-Goo
The network which knows location of all nodes can improve the network capacity and lifetime in location-aware networks. However, localization algorithm of the network has to update its target node location due to mobility of target nodes and intermittent occurrence of interference. The update procedures cause frequent broadcasting and calculation for relocalization; therefore, maintaining the transmission power control (TPC) in the wireless sensor networks (WSNs) is valuable to the network. This paper proposes a new algorithm of transmission power controlled localization for indoor environment. Firstly, we propose minimum spanning tree (MST) based topology control with location error compensation algorithm to improve location accuracy and prevent target nodes from connecting to unstable links in non-line-of-sight (NLOS) condition. Secondly, we use TPC algorithm to improve the network lifetime. Each target node dynamically adjusts the power and the received signal strength (RSS) target by using the TPC algorithm. Experimental results show that the proposed algorithm compensates for location errors in NLOS condition while reducing the transmission power.